Improving socket design to prevent difficult removal of locking screws. Issue 3 (March 2018) - Lin, Chen-Huei; Chao, Ching-Kong; Tang, Yi-Hsuan; Lin, Jinn
Abstract: Introduction: Reports of driver slippage leading to difficult locking screw removals have increased since the adoption of titanium for screw fabrication; the use of titanium is known to cause cross-threading and cold welding. Such problems occur most frequently in screws with hex sockets, and may cause serious surgical complications. This study aimed to improve screw socket design to prevent slippage and difficult screw removal. Materials and methods: Three types of small sockets (hex, Torx, and cruciate) and six types of large sockets (hex, Torx, Octatorx, Torx+ I, Torx+ II, and Torx+ III) with screw head diameters of 5.5 mm were manufactured from titanium, and corresponding screwdrivers were manufactured from stainless steel. The screw heads and drivers were mounted on a material testing machine, and torsional tests were conducted to simulate screw usage in clinical settings at two insertion depths: 1 and 2 mm. Ten specimens were tested from each design, and the maximum torque and failure patterns were recorded and compared. Results: For small sockets in 2 mm conditions, the hex with the largest driver core had the highest torque, followed by Torx and cruciate. In these tests, the drivers were twisted off in all specimens. However, under the 1 mm condition, the hex slipped and the torque decreased markedly. Overall, torque was higher for large sockets than for small sockets. The Octatorx, with a large core and simultaneous deformation of the driver and socket lobes, had the highest torque at almost twice that of the small hex. The hex had the lowest torque, a result of slippage in both the 1 and 2 mm conditions. Torx plus designs, with more designed degrees of freedom, were able to maintain a higher driving angle and larger core for higher torque. Conclusions: The hex design showed slipping tendencies with a marked decrease in torque, especially under conditions with inadequate driver engagement. Large sockets allowed for substantial increases in torque. The Torx, Octatorx, and Torx plus designs displayed better performance than the hexes. Improvements to the socket design could effectively prevent slippage and solve difficult screw removal problems.